2017
DOI: 10.14507/epaa.25.2757
|View full text |Cite
|
Sign up to set email alerts
|

The social networks and paradoxes of the opt-out movement amid the Common Core State Standards implementation: The case of New York

Abstract: Opting out of state standardized tests has recently become a movement-a series of grassroots, organized efforts to refuse to take high-stakes state standardized tests. In particular, the opt-out rates in the state of New York reached 20% in 2015 and21% in 2016. This study aims to illustrate the social networks and examine the paradoxes that have propelled the opt-out movement in New York-the movement's epicenter with the highest opt-out rate in the United States. Drawing on the conceptual frameworks of social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…In a network analysis of Twitter feed about Common Core, Supovitz et al (2015) found that reasons for joining the Test Refusal Movement went far beyond the narrow issues cited by policymakers and the testing industry. Their study, as well as several others (e.g., Strauss, 2013;Wang, 2017) found that many concerns of movement activists involved instruction: a narrowing of the curriculum and too much teaching to the test; lost instructional time due to test preparation and test administration; concerns about the Common Core curriculum; and concerns about loss of freedom and creativity for students and teachers. Other issues had to do with the tests themselves: the costs of the tests (including hardware, infrastructure, and additional personnel); the validity and usefulness of the tests; and fear of data mining.…”
Section: Reasons For Mobilizationmentioning
confidence: 91%
See 1 more Smart Citation
“…In a network analysis of Twitter feed about Common Core, Supovitz et al (2015) found that reasons for joining the Test Refusal Movement went far beyond the narrow issues cited by policymakers and the testing industry. Their study, as well as several others (e.g., Strauss, 2013;Wang, 2017) found that many concerns of movement activists involved instruction: a narrowing of the curriculum and too much teaching to the test; lost instructional time due to test preparation and test administration; concerns about the Common Core curriculum; and concerns about loss of freedom and creativity for students and teachers. Other issues had to do with the tests themselves: the costs of the tests (including hardware, infrastructure, and additional personnel); the validity and usefulness of the tests; and fear of data mining.…”
Section: Reasons For Mobilizationmentioning
confidence: 91%
“…According to a survey of movement participants, the most common forms of activism by individuals were refusing the tests, posting information on social media, discussing with other parents, joining web-based distribution lists, signing petitions, contacting elected officials, and attending demonstrations or protests (Pizmony-Levy and Saraisky, 2016). Wang (2017) conducted an analysis of press coverage and documents in order to identify the movement actors in New York State and their opponents and to understand the networks among these organizations. The test refusal teacher organizations and the test refusal parent groups had the highest degree of centrality in the network of the Test Refusal Movement.…”
Section: Refusal Trends and Protest Interactionsmentioning
confidence: 99%
“…This would allow for exploring the interlocking relationships between SMOs and their role in facilitating change (or stability) within the opt-out movement. Yet another possible direction is to analyze news reports on the opt-out movement (similar to the work of Wang, 2017). Social-movements scholars have used this approach to study changes in SMOs collaboration and the role of networks in the diffusion of protest tactics (e.g., Wang & Soule, 2012;.…”
Section: Discussionmentioning
confidence: 99%
“…In states like New York, families have massively followed calls to boycott the test and, in response to these actions, the government has introduced improvements in the test design and administration. The political influence of this movement also manifests in the fact that 'opt-out parents' have been elected in different district school boards (Wang, 2017).…”
Section: Spreading Like Wildfire But Meeting Firewallsmentioning
confidence: 99%